2018
DOI: 10.5194/tc-12-1027-2018
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Andes snow cover from MODIS data, 2000–2016

Abstract: Abstract. The Andes span a length of 7000 km and are important for sustaining regional water supplies. Snow variability across this region has not been studied in detail due to sparse and unevenly distributed instrumental climate data. We calculated snow persistence (SP) as the fraction of time with snow cover for each year between 2000 and 2016 from Moderate Resolution Imaging Spectroradiometer (MODIS) satellite sensors (500 m, 8-day maximum snow cover extent). This analysis is conducted between 8 and 36 • S … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 84 publications
5
75
0
5
Order By: Relevance
“…The MERRA-2 data set has 576 points in the longitudinal direction and 361 points in the latitudinal direction, corresponding to a resolution of 0.625°× 0.5° (Bosilovich et al, 2016). The MERRA-2 data set has been validated (Reichle et al, 2017) and extensively used for the climatic and hydrological research (Cortés et al, 2016;Lim et al, 2016;Saavedra et al, 2018). In this study, we used two land surface variables (total snow storage land [kg/m 2 ] and snowmelt flux land [kg·m À2 ·s À1 ]) of MERRA-2.…”
Section: Data Sets and Methodsologymentioning
confidence: 99%
“…The MERRA-2 data set has 576 points in the longitudinal direction and 361 points in the latitudinal direction, corresponding to a resolution of 0.625°× 0.5° (Bosilovich et al, 2016). The MERRA-2 data set has been validated (Reichle et al, 2017) and extensively used for the climatic and hydrological research (Cortés et al, 2016;Lim et al, 2016;Saavedra et al, 2018). In this study, we used two land surface variables (total snow storage land [kg/m 2 ] and snowmelt flux land [kg·m À2 ·s À1 ]) of MERRA-2.…”
Section: Data Sets and Methodsologymentioning
confidence: 99%
“…An increasing number of studies recommended that wet-bulb temperature (T w ) should be a better discriminator for the rain-snow partitioning (Behrangi et al, 2018;Ding et al, 2014;Harder & Pomeroy, 2014;Marks et al, 2013;Olsen, 2003;Sims & Liu, 2015;Yamazaki, 2001;Zhang et al, 2011) rather than other variables such as dew point temperature (Behrangi et al, 2018;Marks et al, 2013) or surface air pressure (Dai, 2008). T w is closer to the surface temperature of a falling hydrometeor than T a , representing the cooling effects due to surface evaporation at a constant pressure (Rogers & Yau, 1989) and thus may improve the prediction skill in distinguishing the precipitation phase (Behrangi et al, 2018;Ding et al, 2014). Behrangi et al (2018) suggest that using T w results in the highest prediction skill in the partitioning of precipitation across regions among precipitation partitioning methods that use a single atmospheric variable over global snow-covered regions.…”
Section: Introductionmentioning
confidence: 99%
“…For this topic, a study by Hammond, Saavedra, and Kampf (2018) on global snow zones suggested that temperature has greater influence on snow in lower elevation areas whereas precipitation is more important in high elevations, with mid-elevations displaying a mixture of precipitation and temperature importance. A possible reason was illustrated by Saavedra, Kampf, Fassnacht, and Sibold (2018) by analysing the relative importance of precipitation and temperature to snowpack with different latitude and elevation in Andes, indicating that precipitation may be more important in dry regions whereas temperature may be more important in warm regions. *The two authors contributed equally to this study.…”
Section: Introductionmentioning
confidence: 99%